GABARAPL1 Promotes AR+ Prostate Cancer Growth by Increasing FL-AR/AR-V Transcription Activity and Nuclear Translocation - Su, Bing; Zhang, Lijuan; Liu, Shenglin; Chen, Xiaofan; Zhang, Wei (Frontiers in Oncology, 2019)
The next generation Androgen receptor (AR)-targeted therapies are now in widespread clinical use and prolong prostate cancer (CaP) patient survival. However, the therapies are not curative due to diverse range of resistance mechanisms. AR variants (AR-V), one major mechanism of resistance, has recently gained momentum. Here, we found that GABARAPL1 knockdown inhibits the growth of AR-positive LNCaP and CWR22rv1 CaP cells in vitro and in vivo, decreases AR/AR-V transcription activity and AR nuclear translocation. Pulldown assay shows that both of Full-length (FL)-AR and AR-V were able to interact with GABARAPL1, suggesting that GABARAPL1 may play its role through directly scaffolding AR. The further analysis from Oncomine database showed that negative correlation between GABARAPL1 expression and 5-years survival in CaP cases. Our findings have identified GABARAPL1 as critical regulator of FL-AR/AR-V, suggesting the potential benefit of targeting GABARAPL1 to treat AR-positive CaP that is resistant to next generation AR inhibitors.